A Report of 85 Cases of COVID-19 and Abdominal Transplantation From a Single Center: What Are the Associated Factors With Death Among Organ Transplantation Patients. Issue 1 (23rd September 2020) - Ali Malekhosseini, Seyed; Nikoupour, Hamed; Gholami, Siavash; Shamsaeefar, Alireza; Arasteh, Peyman; Kazemi, Kourosh; Dehghani, Masood; Eghlimi, Hesameddin; Raeisi Shahraki, Hadi; Roozbeh, Jamshid; Rezaianzadeh, Abbas; Nikeghbalian, Saman
Abstract : Background: In this study, we report the epidemiology of COVID-19 among recipients of organ transplantation and evaluate associated factors with death. Methods: We screened 6969 patients who had organ transplantations in our center for COVID-19. Specific data on presentation, clinical course, treatment, and prognosis were acquired. Results: We found 85 patients (66 liver, 16 kidney, 2 kidney-pancreas, and 1 liver-kidney recipient) who acquired COVID-19. Most common symptoms included fever (48.2%), cough (41.2%), myalgia (41.2%), and fatigue (40%). Dyspnea developed in 33% of patients. Overall, one-third of patients had an oxygen saturation of below 90% on admission. Patients were hospitalized for a median (interquartile range) of 9 (5, 13.7) days and had a 33.9% intensive care unit admission rate. Overall, 17 patients (20%) died, which included 31.3% of patients with kidney transplantations and 18.2% of patients with liver transplantations. All 4 pediatric patients in our series died. In our univariate analysis among adults, rates of leukopenia (38.4% versus 13.2%; P  = 0.04), low albumin levels (53.8% versus 10.2%; P  = 0.001), and shorter duration between transplantation and COVID-19 ( P  = 0.02), were higher among patients who died. In our least absolute shrinkage and selection operator regression model, low albumin levels (OR, 4.48; 95% confidence interval, 1.16-17.27) were associated with higher risk of death. Conclusions: This is the largest single-center report on abdominal transplantations and COVID-19. Liver and kidney transplant recipients have an increased risk of mortality compared with the general population due to COVID-19. More specifically, pediatric patients and those with low albumin levels are at higher risks of death due COVID-19.